Judicial Reform in Indonesia: Balancing Independence and Political Interference (Indonesian Court and Justice Review, 2024)
This research explores the complex dynamics of judicial reform in Indonesia, focusing on the ongoing tension between judicial independence and political interference. Since the fall of Suharto's authoritarian regime, Indonesia has undertaken significant reforms to strengthen its democratic institutions, particularly the judiciary. This study examines the extent to which judicial reforms, implemented through constitutional changes and the establishment of independent bodies like the Judicial Commission, have succeeded in insulating the judiciary from political pressures. By analyzing case law, policy documents, and conducting interviews with legal experts, judges, and political analysts, the research identifies key challenges in achieving true judicial independence. The findings indicate that while Indonesia’s judiciary has made strides in reducing political influence, persistent issues—such as corruption, political patronage, and limited accountability—continue to undermine its autonomy. Furthermore, the study highlights the role of political elites in shaping judicial decisions and the ways in which these influences manifest in high-profile legal cases. The research argues that while reforms have created legal frameworks to support judicial independence, the judiciary remains vulnerable to external pressures unless broader political and institutional changes are made. The study contributes to the debate on the balance between judicial independence and political interference, offering recommendations for strengthening the rule of law in Indonesia and ensuring a more impartial judicial system.